Detection of Cadmium by using Ionic Liquid Cellulose based Thin Layer - Syahraini Sulaiman, Siti; Farahiyah Wan Kamarudin, Wan; Mohd Zain, Zainiharyati; Azri Ab Rani, Mohd; ., . (International Journal of Engineering and Technology, 2018)
Ionic liquids have been successfully demonstrated as potential polymer electrolyte with high in conductivity. For sensing application field, ionic liquids based on detection method, performs uniquely with regard to sensing external environments. In this study, ionic liquid cellulose polymer electrolyte was successfully prepared for sensing layer of electrochemical sensor. The ability and sensitivity of the prepared ionic liquid cellulose based thin film as sensing layer on the electrochemical sensor was tested to detect cadmium in wastewater sample by using cyclic voltammetry, (CV). The optimization process was carried out, in which to ensure the electrochemical sensor could detect the cadmium at the best operating conditions. The selection of optimization process involved the effect of pH of the acetate buffer as supporting electrolyte and the effect of scan rate of the electrochemical sensor. The optimum pH of acetate buffer was 6.5 and the optimum scan rate of electrochemical sensor was 0.1 V/s. These optimized conditions were applied in detection of cadmium in the standard and wastewater sample solutions. The amount of cadmium in the wastewater sample was undetectable or below detection level. The sensitivity of the electrochemical sensor was compared to ICP-OES and the result showed that the electrochemical sensor was as applicable as ICP-OES since it can detect the amount of cadmium as low as ppb concentration. The use of ionic liquid cellulose based thin film as sensing layer of electrochemical sensor is a good alternative to detect the cadmium.Â